The monster-in-law effect: Linking qualitative observations to quantitative analysis on household structure, migration and empowerment in Nepal - Pereira, Audrey (International Food Policy Research Institute, 2019)
Presented by Audrey Pereira (International Food Policy Research Institute), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.